The Origin and Evolution of Bladder Cancer Stem Cells - Tan, Jiufeng; Wang, Yao; Sun, Lihui; Xu, Siqi; Li, Charles; Jin, Xuefei (Frontiers in Cell and Developmental Biology, 2022)
Bladder cancer is the most common malignant tumor of the urinary system. Bladder cancer stem cells (BCSCs) play key roles in tumor initiation, metastasis, relapse and drug-resistance. Investigation of BCSCs is of great value. On the basis of a review of normal bladder stem cells and universal cancer stem cells (CSCs), we summarize the origin of BCSCs, isolation and identification of CSCs from bladder cancer, signaling pathway of BCSCs, BCSCs targeted therapy, and relationship of BCSCs with non-muscle invasiveness and muscle invasiveness. This review aims to provide better elucidation about BCSCs, and provide constructive data for classification, prognosis, treatment and early intervention of bladder cancer.